The Institute of Chartered accountants of Nigeria : membership year book 1980 - The Institute of Chartered Accountants of Nigeria; Institute of Chartered Accountants of Nigeria (Lagos, Nigeria : Institute of Chartered Accountants of Nigeria, 1980)
This book provides a detailed account of some of the activities of the institute of chartered accountants of Nigeria with inclusion of aims and objectivity. The book further enlisted the details of all the registered members in 1980.
asm 14/02/2019
Ref
Keywords: Accountants; Directories; Nigeria